PENGARUH PEMBERIAN PROBIOTIK PADA MEDIA AIR TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN LELE (Clarias sp.) - Febya Rizki Hasibuan; Eri Yusni (AQUACOASTMARINE, 2018)
Catfish (Clarias sp.) is a freshwater fish that popular to be cultived and consumed. The most important factors growth and survival rate as well a sufficient feed requirements.. The objective of this study aims to the effect of proboitic in water with growth and survival rate of fish. The research was conducted from march to mei 2018. During these study, the fish were give commercial feed and added probiotic in water. The feeding calculated 5% from body weight. The frequency of feeding were give 3 time a day at 09:00 AM ; 13:00 PM ; 18:00 PM. The design that have been used in this study was complete Randomized design with 3 treatment and 3 repitions namely : P1 (1,5 ml/L), P2 (2 ml/l), P3 (2,5 ml/L). The results of these research were used analyzed by SPSS. The result showed that the given probiotic significantly affected of the length and weight of fish but did not significantly affect for survival rate. The higher growth of length and weight was found with P3 and mixed of probiotic 2,5 ml/L and the higher survival rate was found 77% in P3 and mixed of probiotic 2,5 ml/L.Keyword: Catfish, Probiotics, Growth.